Wave-induced liquefaction of the seabed around a single pile considering pile–soil interaction. Issue 1 (2nd January 2018) - Zhu, Bin; Ren, Jie; Ye, Guan-Lin
ABSTRACT: The analysis of wave-induced liquefaction of seabeds is of profound importance for offshore structures such as wind turbines and oil platforms. The seabed around pile foundations is subjected to two effects, vertical wave loads and the lateral pile–soil interactions induced by the rocking of super structures. This paper numerically studies the excess pore pressure responses of the seabed around a pile when both effects are considered. Numerical analysis is conducted using an in-house developed, effective stress-based, three-dimensional finite element code. The mechanical behaviors of the seabed are simulated by a kinematic hardening constitutive model that can describe the cyclic mobility of soils. Comparing the results of the seabed around a pile and the seabed with no pile foundation shows that the excess pore pressures accumulate faster when both of the effects are considered. Water depth plays an essential role in determining whether the effect of pile–soil interaction on excess pore pressures can be neglected. In deep waters, the excess pore pressure response mainly derives from the effect of the pile rocking, while the influence of vertical wave pressure on the seabed is relatively small. However, in shallow waters, both of the effects are significant.